New physics from warped compact extra dimensions: from model building to colliders signals - Oliveira, Alexandra Carvalho Antunes de [UNESP] (2014)
The Higgs field of the Standard Model theory for elementary particles and interactions can be realized as a composite state from an underlying strong sector. Such hypothesis is very attractive as an ultraviolet completion of the Standard Model since it solves the hierarchy and avoids naturalness problems. The standard perturbative methods cannot be used in the context of strongly interacting theories, however thyose can be broadly describes in terms of extra dimensional models of gravity. We focus on the case of one additional Warped compact Extra Dimension (WED). The generic signatures of this scenario are the manifestation of heavy gravity particles, associated with the five dimensional metric, that couples with the Standard Model matter leading to direct collider signatures. The heavy gravity particles couples to the Higgs sector. The Higgs discovery had oponed a new investigation channel to LHC direct detection that is the di-higgs final state. We use Monte Carlo techniques to study the analysis strategies that would lead to a best recognition of new resonances decaying to a pair of higgses in hadron colliders, that can be interprets as the gravity particles. We finally present resonance searches performed with data taken by the CMS experiment on the 8 TeV LHC run. The results are interpreted as the gravity particles signatures in the WED context